What Drives the POLONIA Spread in Poland? - Lu, Yinqiu (IMF Working Papers; Working Paper ;, 2012)
Since the start of the 2008 - 09 financial crisis, the Polish Overnight Index Average (POLONIA) has persistently been below the policy rate, suggesting a limited influence of the NBP's open market operations on the short-term interbank rate. In this regard, this paper analyzes the behavior of the POLONIA spread and explore several potential factors that could influence the spread. An empirical analysis confirms that the negative POLONIA spread is related to a few factors, which include the existence of the structural liquidity in the banking system; bank's unwillingness to lock up liquidity in the NBP bills; the frontloading of banks' fulfillment of the reserve requirements; and external market sentiment. The analysis also shows the effectiveness of the NBP's responses to the financial crisis and structural liquidity surplus.